The Way to happiness a common sense guide to better living. - Hubbard, L. Ron (La Fayette Ron) 1911-1986 (L. Ron Hubbard Library, 2010)
"A powerful film presenting the 21 precepts of today's most widely used common sense moral code."--Container.